KEPELBAGAIAN PERWAKILAN SISTEM ALGEBRA KOMPUTER DALAM PEMBINAAN PENGETAHUAN BENTUK GRAF FUNGSI KUADRATIK (Sains Humanika, 2006)
Computer Algebra Systems (CASs) are the technologies that had been developed for Mathematics research and also as a medium in computer-based learning. CASs can be used for expansion and simplification of algebraic functions and graph by switching (transforming) betweensymbolic, numerical, and graphical capabilities. The purpose of this research is to study the potential of various representations in a CAS for construction of a meaningful knowledge of graphical forms in quadratic functions. Three types of representations known as numerical, symbolic, and graphical were coordinated by students while constructing the knowledge. This research employed the qualitative approach with a sample of 8 secondary school students from a residential school in Terengganu. Data were collected through observations, clinical interviews, and analysis of students’ written assignmentsafter a guided exploration. The results show that the students were able to construct a meaningful knowledge of graphical forms of quadratic functions by coordinating various types of representations.
Keywords: Knowledge representations; qualitative approach; Mathematics education; quadratic functions; graphical forms